Peripheral embolism as first and only clinical symptom of a true aneurysmal degeneration of the radial artery after ligation of a radiocephalic fistula. Issue 3 (May 2023) - Malbecq, Clémentine; Hammer, Frank; Pochet, Jean-Michel; Labriola, Laura; Kanaan, Nada; Devresse, Arnaud; Lambert, Catherine; Mourad, Michel; Snoeijs, Maarten; Darius, Tom
True aneurysmal degeneration of the inflow artery after arteriovenous fistula ligation is extremely rare. Pain is the most common symptom and surgical treatment by an autologous venous bypass is considered as the treatment of choice with good long-term results. We present a patient with peripheral embolism as first and only symptom leading to the diagnosis of a true aneurysmal degeneration of the entire left radial artery. It was discovered 5 years after the ligation of his radiocephalic fistula. As illustrated by this case, a conservative treatment by antiplatelet and anticoagulation therapy should be considered a satisfying alternative to the standard bypass surgery in patients with anatomical variations (e.g. an incomplete arterial palmar arch) since the latter include a higher risk of postoperative ischemic complications.